2021
DOI: 10.1093/hropen/hoaa063
|View full text |Cite|
|
Sign up to set email alerts
|

The ethics of preconception expanded carrier screening in patients seeking assisted reproduction

Abstract: Expanded carrier screening (ECS) entails a screening offer for carrier status for multiple recessive disorders simultaneously and allows testing of couples or individuals regardless of ancestry or geographic origin. Although universal ECS—referring to a screening offer for the general population—has generated considerable ethical debate, little attention has been given to the ethics of preconception ECS for patients applying for assisted reproduction using their own gametes. There are several reasons why it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Nonetheless, it is incumbent upon the states to substantiate and justify the decisions and approaches they choose to undertake, in order to strike a fair balance between competing private and public interests and reconcile the legitimate hopes, needs, desires, and aspirations of all those involved [43,44]. That is to be viewed as part and parcel of the broader duty each country has committed to fulfilling, via the signing of international treaties, in regards to civil and human rights enforcement [45][46][47]. The very constitution of the WHO itself asserts beyond the shadow of a doubt that "the enjoyment of the highest attainable standard of health is a fundamental right of every human being without distinction of race, religion, political belief, economic or social condition," and that national governments must be held responsible "for the health of their peoples which can be fulfilled only by the provision of adequate health and social measures."…”
Section: Medically-assisted Procreation As An Essential Tool For Upholding Reproductive Rights and Autonomymentioning
confidence: 99%
“…Nonetheless, it is incumbent upon the states to substantiate and justify the decisions and approaches they choose to undertake, in order to strike a fair balance between competing private and public interests and reconcile the legitimate hopes, needs, desires, and aspirations of all those involved [43,44]. That is to be viewed as part and parcel of the broader duty each country has committed to fulfilling, via the signing of international treaties, in regards to civil and human rights enforcement [45][46][47]. The very constitution of the WHO itself asserts beyond the shadow of a doubt that "the enjoyment of the highest attainable standard of health is a fundamental right of every human being without distinction of race, religion, political belief, economic or social condition," and that national governments must be held responsible "for the health of their peoples which can be fulfilled only by the provision of adequate health and social measures."…”
Section: Medically-assisted Procreation As An Essential Tool For Upholding Reproductive Rights and Autonomymentioning
confidence: 99%
“…In recent years, as more genes associated with serious genetic conditions have been discovered and genetic testing technologies have advanced, the prospect of offering reproductive genetic carrier screening (RGCS) more broadly, rather than only to those known to have a higher chance 1 of transmitting a rare genetic condition, has arisen (Antonarakis 2019 ; Delatycki et al 2020 ; Rowe and Wright 2019 ). Fertility clinics may also offer RGCS to couples undertaking assisted reproduction, regardless of their family history (de Wert et al 2021 ). Such initiatives have been underscored by increasing awareness of the benefits of offering carrier screening to anyone intending to have children (Henneman et al 2016 ; McClaren et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…This guidance might open the door to investigating whether ECS in a fertility setting in the Netherlands would be proportionate and acceptable to couples and professionals (188). Introduction of ECS in a fertility setting is supported by several studies, mainly in the United States (US), which have suggested that healthcare professionals welcome the possibility of ECS for couples undergoing fertility treatment (38,39).…”
Section: Choice Of Primary Care (Nl) and Fertility Setting (Uk)mentioning
confidence: 99%
“…In 2021, ESHRE published ethical guidance regarding the introduction of ECS for couples seeking assisted reproduction using their own gametes. This guidance might open the door to investigating whether ECS in a fertility setting in the Netherlands would be proportionate and acceptable to couples and professionals (188).…”
Section: Choice Of Primary Care (Nl) and Fertility Setting (Uk)mentioning
confidence: 99%
See 1 more Smart Citation